Pemantauan Konsentrasi Gas SO2 di Sekitar Gunung Sinabung Menggunakan Citra Satelit Sentinel-5 Precursor - Sihotang, Elstri; Artaningh, Febzi; Anggrainia, Tania Septi; Sakti, Anjar Dimara; Agustan, Agustan (Jurnal Penginderaan Jauh Indonesia, 2020)
Monitoring of SO2 Gas Concentration Around Mount Sinabung Using Sentinel-5 Precursor Satellite Imagery Abstract. Mount Sinabung is a mountain type A that is still active. Mount Sinabung is located in North Sumatra Province, Karo Regency. Mount Sinabung eruption does affect not only the region but also the area around the mountain. One of the substances that were sprayed by the volcano during the outbreak was SO2 gas. SO2 gas is an essential parameter for determining air quality. SO2 gas is in the atmosphere through a natural process and anthropogenic process. The data of SO2 gas was obtained by utilizing the Sentinel-5P record results. Data Sentinel-5P was processed and analyzed to be able to determine the SO2 gas concentration in the area surrounding Mount Sinabung and also changes in the SO2 gas concentrations in several areas. In general, the highest SO2 gas concentration was at the crater of Mount Sinabung. However, on 22 July 2019, the SO2 gas concentrations in Deli Serdang Regency were higher, around 75% of SO2 gas concentrations in the crater area. This research may also indicate that Sentinel-5P data can be used to monitor gas in the atmosphere. Keywords: Mount Sinabung; Eruption; SO2; air quality; Sentinel-5P.